Gendered intra-household contributions to low-input dairy in Senegal - Walugembe, M.; Tebug, Stanly Fon; Tapio, M.; Missohou, Ayao; Juga, J.; Marshall, Karen; Rothschild, Max F. (2016)
A survey was conducted in two sites of Senegal to determine the intra-household gender roles in the Senegal dairy cattle systems. Two surveys, baseline and longitudinal were conducted and the main survey respondents were the households heads. Households were grouped into two levels (higher or lower) of market orientation using the longitudinal household milk production data. Baseline survey results revealed that adult males (> 15 years of age) were responsible for the costs and decision making of most of the dairy related activities though less so when production was quite low. Adult males, hired males (> 15 years of age), and any other household members, except the female gender were the main labor source for the dairy activities. When comparing who received income from milk sales, income from lower market orientated households went to females for a larger proportion of households, than in higher market orientated households.